Uric acid as a biomarker for pregnancy induced hypertension (Panacea Journal of Medical Sciences, 2020)
Background: Pregnancy induced hypertension is the most common complication of pregnancy. It affects 5-7% of pregnant women. Pregnancy induced hypertension is characterized by vasospasm which is associated with platelet aggregation and reduced uteroplacental flow. In addition to these, altered renal function tests can also worsens the condition. This influences the maternal as well as fetal outcome.Aims: To prevent the complications of pregnancy induced hypertension and for proper management of these cases present study was conducted.Materials and Methods: The present study was conducted in 300 subjects grouped into 120 cases of normal pregnancy, 150 cases of pregnancy induced hypertensives, 30 cases of eclamptics and serum uric acid level was measured in these.Results and Discussion: elevated level of serum uric acid was seen with increase in gestation period and rise in diastolic blood pressure. The p- value was estimated by student t-test in different groups and was found to be< 0>Conclusion: Hence Serum Uric acid is the significant and reliable indicator for pregnancy induced hypertension to prevent the fetal and maternal mortality and morbidity.